A new multivariate generalized log-double exponential family of distribution of kind-2. Issue 1 (2nd January 2018) - David Sam Jayakumar, G. S.; Solairaju, A.; Sulthan, A.
Abstract: This paper proposed a Kind-2 distribution of the multivariate generalization of log-double exponential family of distributions. Further, the constants of the proposed distribution namely it's Marginal, Multivariate conditional distributions and generating functions also expressed in a closed series expansion form. Many special cases of this distribution are derived and the location, scale, shape parameters determines the family of some existing known distributions such as familiar bivariate, mixtures of bivariate distributions, generalized and multivariate distributions are mushroomed as subclasses of the proposed multivariate generalized log-double exponential family of distribution of kind-2.